Design and implementation of high voltage DC generation system based on push-pull inverter integrated with Cockcroft-Walton - Mardiyah, Luthfiyyatun; Syakur, Abdul; Setiawan, Iwan (Institute of Advanced Engineering and Science, 2024)
High-voltage DC generation is essential for industrial, medical, and scientific applications, such as X-ray machines, particle accelerators, and electrostatic precipitators. Existing high-voltage DC generators face challenges such as high cost, complexity, and inefficiency. A simplified and cost-effective solution that can reliably generate high-voltage DC from a low DC power supply is needed. This paper discusses the design and implementation of a high-voltage DC generator with a low-voltage DC power supply input. The generator employs a push-pull inverter to transform the DC 12 V voltage into AC 400 V at a frequency of 20 kHz. A Cockcroft-Walton circuit, comprising a positive and a negative Cockcroft-Walton circuit, then steps up this voltage. The Arduino Nano microcontroller uses pulse width modulation (PWM) signals to control the system. This research aims to provide a reliable and economical high-voltage DC voltage generation system for various applications. We discuss the design process and hardware implementation in detail. We set the target output voltage of this hardware at 10 kV DC. MATLAB/Simulink simulation software verifies the performance of the proposed high-voltage generator, and hardware implementation validates its effectiveness. The proposed high-voltage DC generator's hardware tests successfully produced an output voltage of 14.12 kV DC.